Gerakan Bumil Setia di Desa Sembubuk Muaro Jambi Tahun 2023 - Suryanti, Yuli; Suryani, Suryani; Soleh, Evrina Solvia (Jurnal Abdimas Kesehatan (JAK), 2025)
The MMR target in 2024 is 183 per 100,000 live births. This figure is still very far from the current condition of 305 per 100,000 live births. Likewise, the estimated prevalence of stunting in toddlers in 2024 with a target of 14% is still far from the current condition of 24.4%. In order to accelerate the reduction of MMR and the prevalence of stunting in toddlers, one of the efforts made is through increasing the quality of maternal health services (antenatal care) to 6 times. Maternal health services 6 times have only reached 2,583,073 pregnant women out of the target of 4,897,988 pregnant women, and the number of pregnant women who received Hb examination services is lower, namely 1,474,723 mothers, those examined by doctors at the 1st visit (K1) were 771,936 mothers, and those examined by doctors at the 5th visit (K5) were 543,510 mothers. The Bumil Setia Movement refers to the Healthy Pregnant Women Movement program from the Indonesian Ministry of Health which seeks to reduce stunting in Indonesia starting from before pregnancy, during pregnancy, and after birth. The Bumil Setia activity aims to increase awareness and compliance of pregnant women in undergoing prenatal checkups, maintaining health during pregnancy, and improving understanding of managing food/diet during pregnancy. This activity is carried out by providing information and education both in groups and individually by conducting home visits to pregnant women in Sembubuk Village. There has been an increase in maternal compliance in checking their pregnancy from previously only 48.2% to 76.5%. Most pregnant women have regularly attended prenatal classes for 4 times (82.4%). 58.8% of pregnant women who consume iron supplements tablets > 90 tablets. Most pregnant women with Hb levels > 11gr% are 12 pregnant women (70.6%).